Electrodeposition of tin selenide thin film semiconductor: effect of the electrolytes concentration on the film properties - Zainal, Zulkarnain; Ali, Ali Jimale; Kassim, Anuar; Hussein, Mohd Zobir (Elsevier Science, 2003)
Tin selenide semiconductor films have been potentiostatically deposited onto a tin substrate from an aqueous solution containing SnCl2 and Na2SeO3. Deposition at various concentrations was attempted in order to investigate the effect of the electrolytes concentration on the film properties and to determine the optimum bath composition. The structure, morphology and photoactivity of the films were studied using X-ray diffraction, scanning electron microscopy and linear sweep photovoltammetry techniques. The semiconducting property of the deposit is strongly affected by the electrolytes concentration. The optimum bath composition was found to be 0.010 M for SnCl2 and 0.015 M for Na2SeO3.